Hepatic stellate cell activation by TGFβ induces hedgehog signaling and endoplasmic reticulum stress simultaneously. (April 2022) - Solhi, Roya; Lotfi, Abbas Sahebghadam; Lotfinia, Majid; Farzaneh, Zahra; Piryaei, Abbas; Najimi, Mustapha; Vosough, Massoud
Abstract: Activation of hepatic stellates (HSCs) is known as the major cause of initiation and progression of liver fibrosis. A wide array of events occurs during HSC activation including induction of hedgehog (Hh) signaling and endoplasmic reticulum (ER) stress. Targeting HSC activation may provide promising insights into liver fibrosis treatment. In this regard, establishing in vitro models which can mimic the molecular pathways of interest is very important. We aimed to activate HSC in which Hh signaling and ER stress are stimulated simultaneously. We used 5 ng/ml TGFβ to activate LX-2 cells, HSC cell line. Gene expression analysis using qRT-PCR, immunostaining and immunoblotting were performed to show HSC activation associated markers. Furthermore, the migration capacity of the TGFβ treated cells is evaluated. The results demonstrated that major fibrogenic markers including collagen1a, lysyl oxidase, and tissue inhibitor of matrix metalloproteinase 1 genes are up-regulated significantly. In addition, our immunofluorescence and immunoblotting results showed that protein levels of GLI-2 and XBP1, were enhanced. Moreover, we found that TGFβ treatment reduced the migration of LX-2 cells. Our results are compatible with high throughput data analysis with respect to differentially expressed genes of activated HSC compared to the quiescent ones. Moreover, our findings suggest that quercetin can reduce fibrogenic markers of activated HSCs as well as osteopontin expression, a target gene of hedgehog signaling. Highlights: TGFβ, the main profibrogenic cytokine, can induce hedgehog signaling and ER stress simultaneously in hepatic stellate cells Collagen secretion and fibrogenic markers are increased following TGFβ treatment in activated hepatic stellate cells (aHSCs) Gene set enrichment analysis revealed that collagen- related signaling pathways are among the most enriched pathways in aHSCs Quercetin, inhibits hedgehog signaling and reduces fibrogenic markers of TGFβ-activated hepatic stellate cells